2013
DOI: 10.1038/cddis.2013.303
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivation of retina by light in mice leads to photoreceptor cell death mediated by VEGF and retinal pigment epithelium permeability

Abstract: Light toxicity is suspected to enhance certain retinal degenerative processes such as age-related macular degeneration. Death of photoreceptors can be induced by their exposure to the visible light, and although cellular processes within photoreceptors have been characterized extensively, the role of the retinal pigment epithelium (RPE) in this model is less well understood. We demonstrate that exposition to intense light causes the immediate breakdown of the outer blood–retinal barrier (BRB). In a molecular l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 53 publications
3
41
1
Order By: Relevance
“…Recent studies show that RPE is adversely affected by light exposure (48). We observed the involvement of the RPE in the phagocytosis of GCAP1 and rhodopsin-positive membranes (Fig.…”
Section: Our Findings On Arr1mentioning
confidence: 50%
“…Recent studies show that RPE is adversely affected by light exposure (48). We observed the involvement of the RPE in the phagocytosis of GCAP1 and rhodopsin-positive membranes (Fig.…”
Section: Our Findings On Arr1mentioning
confidence: 50%
“…It has been shown that hyper-activation of the retina via bright-light exposure leads to photoreceptor cell death in mice due, in part, to increased VEGF-mediated RPE permeability [39]. To investigate the effects of the αCT1 peptide on RPE cell integrity, RPE damage was triggered using a light-damage model (3000 lux of white light for 3 hours) in Balb/c mice.…”
Section: Resultsmentioning
confidence: 99%
“…In albino BALB/c mice, spatial visual acuity was under the limit of detection already at baseline, even before exposure to SI, so this functional measure could not be followed in this strain (similar absent or severely reduced OKT responses in albino mice have been previously reported by others). [30][31][32] Electrophysiological Retinal Function…”
Section: Optimizing Intraperitoneal Sodium Iodate Dosementioning
confidence: 99%